EFEKTIFITAS LATIHAN ACTIVITY DAILY LIVING DALAM MENINGKATKAN KEMANDIRIAN DAN MENURUNKAN KECEMASAN PADA PASIEN GANGGUAN TULANG BELAKANG DI RSUD PROF DR DR MARGONO SOEKARJO PURWOKERTO - Woro Hapsari; Khodijah .; Taskurun Akhyari (UNIVERSITAS BHAMADA SLAWI, 2015)
Spinal disorder is an injury or disorder of the cervical, and lumbar vertebral traumatic fall from a height, traffic accidents, sports accidents tumor and infection causing neurological deficits, the occurrence of paraplegia caused by the loss of a complete sensory and motor, bowel and bladder disorders, dysfunction sexual, autonomic desrefleksia problems arising from the disorder is immobility, weakness, and the inability of the result is the inability to care for themselves, the individual is not able to do the need to maintain and improve the well-being according to the concept of Dorothea Orem self care. Daily Living Activity exercises that include bowel, bladder training, grooming, feeding, personal hygine can improve self-care and as a basis for the ful fillment of self-care. His study uses an experimental design approach prepre-testand post test without control. Samples accidental sampling independent variables: exercise Activity Daily Livingdependent variable independence and anxiety. Paired t-test results o fthe independence of the value of .001 (p<0.05), the results Paired t-test anxiety with a value of .015 (p<0,05). Conclusions significant difference value independence and anxiety before and after exercise Activity Daily Living, exercise daily living activity can increase independence and decrease anxiety in patients with spinal disorders